Drivers of private consumption in the era of financialisation: new evidence for the European Union countries - Barradas, Ricardo (2018)
This paper provides an empirical assessment of the effects of financialisation on private consumption using panel data for all 28 European Union countries from 1995 to 2015. According to the post Keynesian literature, financialisation exerts two contradictory effects on private consumption, notably a negative one linked to the fall of households’ labour income and a positive one related to the increase of households’ (financial and housing) wealth. A private consumption equation was estimated by including three variables linked to financialisation (labour income, financial wealth and housing wealth) and five additional control variables (lagged private consumption, short-term interest rate, long-term interest rate, inflation rate and unemployment rate). Our results confirm that financialisation has been detrimental to private consumption in the EU countries as a whole, and more specifically in the Euro area countries, as the beneficial wealth effect has not been sufficient to compensate for the prejudicial income effect. The fall of households’ labour income has even been the highest constraint on private consumption in the Euro area countries.